KESENIAN WAYANG PADA MASA KLASIK DI JAWA - Rita Istari (Berkala Arkeologi, 2003)
The name of wayang kulit only became known during the reign of Airlangga, as is found in Kakawin Arjunawiwaha. Then from Kakawin Bharatayudha it can be seen that the puppet show has been accompanied by gamelan and so on, although it is not as complete as it is now. From Kakawin Wrettasancaya, who was younger, it is known that the puppets at that time were already colored. This is also proven by the puppet reliefs on the temples, even though in fact the temples were younger than Arjunawiwaha, Wrettasancaya and Ghatokacasraya's kakawin, but of course the relief sculptors imitated the pattern of images of shadow puppet figures that were already known in previous times.